Factores de riesgo para adquirir diabetes mellitus tipo II en los estudiantes de los 6tos cursos del colegio Técnico Daniel Álvarez Burneo - Armijos Ordóñez, Alex Patricio (2016)
Diabetes Mellitus type 2 (DM2) has an incidence has gradually increased in recent years, there are also changes in the age of onset of the disease, which was typical of adulthood, maintaining its prevalence even in this group; the presence of this disease in adolescence is due by overweight and obesity, which is closely related to type 2 diabetes. Because of this reality my research project has the overall objective to know what the risk factors are to acquire diabetes mellitus type II students 6 cough courses Technical College Daniel Alvarez Burnet city of Loja, determine the associated factors, identify family medical history and set the BMI this study is descriptive, as it allowed detailing the causes that could be associated to the development of DM2, the implementation of the survey addressed to the study group was also considered, including questions to determine the risk factors to which they are exposed the / adolescent years, and together a questionnaire applied to parents, mothers and / or guardians. The sample is represented by 243 students of which 133 are women and 110 are men, between the data obtained evidenced that the age of the people under study, ranging from 17 to 19 years. The results obtained were as follows: 14.38% altered pressure, consume snuff 13.99%, 34.57% consume alcohol, 7.41% have a sedentary lifestyle, 46.92% have a family with obesity and a 26.33% of the students presented obesity. Keywords: Diabetes Mellitus, Prevalence, Risk Factor